Laparoscopic liver resection for liver metastasis of leiomyosarcoma of the thigh: a case report - Shoichi Tsuzaka; Yoh Asahi; Toshiya Kamiyama; Tatsuhiko Kakisaka; Tatsuya Orimo; Akihisa Nagatsu; Takeshi Aiyama; Takeyuki Uebayashi; Hirofumi Kamachi; Masatake Matsuoka; Kento Wakabayashi; Takuya Otsuka; et al. (Surgical Case Reports)
Abstract Background Although there is no established treatment strategy for liver metastasis of leiomyosarcoma, liver resection has been reported to be effective in some cases. However, almost all liver resections performed for liver metastasis of primary leiomyosarcoma are reported to be open resections, and there are few reports of liver resection performed by laparoscopy. Here, we report a case of laparoscopic liver resection for liver metastasis of a leiomyosarcoma in the right thigh. Case presentation An 80-year-old man was diagnosed with leiomyosarcoma of the right thigh with liver metastasis. The primary tumor was first resected, and he was discharged on the 25th postoperative day. Four months after primary tumor resection, a laparoscopic right posterior sectionectomy was performed. There were no postoperative complications, and the patient was discharged on the 11th postoperative day with a histopathological diagnosis of liver metastasis of leiomyosarcoma and negative resection margins. Currently, 9 months have passed since the resection of the primary tumor, and 5 months have passed since the laparoscopic liver resection; there is no recurrence. Conclusions The liver metastasis of leiomyosarcoma was successfully removed, with good short-term outcomes after the laparoscopic liver resection. Laparoscopic liver resection seems to be effective for liver metastasis of leiomyosarcoma, which is characterized by a high recurrence rate after surgery. However, more case studies may be necessary to examine the effectiveness and long-term results of laparoscopic liver resection for the treatment of liver metastasis of leiomyosarcoma.